REPRESENTASI RELIGI DALAM NOVEL AYAT-AYAT CINTA 2 KARYA HABIBURRAHMAN EL SHIRAZY - Ida Rufaida (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
This study aimed to describe everything about the religiosity of the novel Love Verses 2, both with regard to religious values, religious dimension, as well as the representation of religion in society. The data were derived from novel Love Verses 2 Habiburrahman El Shirazy, first printing November 2015, contains 690 pages, published by Republika. Data collected by technical literature by using descriptive method qualitative sociological approach. In this study, it appears that the value of religiosity contained in this is the value of worship, moral values, the value of the trust, the value of exemplary and sincere. in addition, religiosity is also present in the religious dimension that includes the dimension of experience, knowledge dimension of religion, and the dimensions of practice or Consequences. Representation of religion in society in this novel, seen how efforts to realize a harmonious life, always formed two attitudes among religious circles. First, with respect and respect other faiths because of an interest, such as political or other interests. Second, with respect and respect other faiths because he would be the religious teachings of the Lord. Awareness realize harmony between religions is a very important thing.